KELEBIHAN SERTA KEKURANGAN PERKERASAN BERASPAL DAN BETON - M. Sjahdanulirwan (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
or servicing the passage of vehicles, on the top of sub-grade are consist of pavement, so that the receiving load can be distributed to the value that can be borne of that sub-grade. From efficiency point of view, pavement which are build on the top of subgrade, usually from the bottom to up are namely sub-base, base, and surfacing, with strength are higher to the top. Sometimes, according to design calculation, below the surfacing, there is only base or sub-base (plat form) only, then direct to sub-grade. Material for road pavement also varied, commonly from aggregate, bituminous, or cement concrete. This paper review the advantages and disadvantages the surfacing made from bituminous and concrete, with particular attention to cost, time, durability and strength, comfort and safety, construction nd equipment aspects, and environment impact. Then, the paper describes sinthesis and innovative which are available to reduce the disadvantages of each type of pavement. Keywords: bituminous pavement, concrete pavement, synthesis and innovative